The Effect of Self-Esteem and Self-Control on The Mathematical Creative Thinking Ability Student of SMP Negeri 4 Purwokerto - Sulistiani, Sisfi (International Journal of Research in Mathematics Education, 2024)
This study aims to determine whether there is an influence collectively or individually between self esteem and self control variables on the mathematical creative thinking ability of class IX at SMP N 4 Purwokerto. The type of research used is quantitative research with survey methods. The population in this study were all 279 students in class IX at SMP Negeri 4 Purwokerto. Samples were obtained as many as 165 students based on the Slovin formula, which were taken using simple random sampling technique. Data collection was carried out through tests of mathematical creative thinking abilities and self esteem and self control questionnaires. Data analysis techniques were performed using simple linear regression and multiple linear regression, as well as statistical t tests and statistical F tests. The results of this study were 1) there was the influence of self esteem on mathematical creative thinking skills of class IX students of SMP Negeri 4 Purwokerto. This is shown based on the calculated t value of (2.937) > t table (1.974), with the regression equation = 6,173 + 0,846X1. 2) there was the influence of self control on mathematical creative thinking skills of class IX students of SMP Negeri 4 Purwokerto which is shown based on the value of t count (4.234) > t table (1.974), with the regression equation = 4,518 + 0,891X2. 3) there is the influence of self esteem and self control simultaneously on the ability to think creatively mathematically in class IX students of SMP Negeri 4 Purwokerto, with the acquisition of Fcount (54.037) > Ftable (3.051). The magnitude of the influence is determined by the value of the coefficient of multiple determination, which is 40%, meaning that 60% of students' mathematical creative thinking ability is influenced or determined by other factors. The multiple regression equation that is formed is = -2,872 + 0,403X1 + 0,583X2, meaning that between the variables self esteem and self control on students mathematical creative thinking ability has a positive correlation, and both have a very positive and significant effect. So, with a higher level of self esteem and self control of students, the ability to think creatively mathematically will increase.